Food insecurity during the COVID-19 pandemic who use drugs in Vancouver, Canada - Tyson Singh Kelsall; Kora DeBeck; Cameron Grant; Pamina Gorbach; M-J Milloy; Kanna Hayashi (Cambridge University Press, 2023)
Abstract Objective: To examine prevalence and factors associated with food insecurity among people who use drugs (PWUD) during the first year of the COVID-19 pandemic and the overdose crisis. Design: This cross-sectional study employs multivariable logistic regression to identify factors associated with self-reported food insecurity. Participants: PWUD who are part of three community-recruited cohorts. Setting: Interviews conducted in Vancouver, Canada, via phone between July and November 2020 in adherence to COVID-19 safety procedures. Results: Among 765 participants, including 433 (56·6 %) men, eligible for this study, 146 (19·1 %; 95 % CI: 16·3 %, 21·9 %) reported food insecurity in the past month. Of the participants reporting food insecurity, 114 (78·1 %) reported that their hunger levels had increased since the beginning of the pandemic. In multivariable analyses, factors independently and positively associated with food insecurity included: difficulty accessing health or social services (adjusted OR (AOR) = 2·59; 95 % CI: 1·60, 4·17); having mobility difficulties (AOR = 1·59; 95 % CI: 1·02, 2·45) and engaging in street-based income generation (e.g. panhandling and informal recycling) (AOR = 2·31; 95 % CI: 1·45, 3·65). Conclusion: Approximately one in five PWUD reported food insecurity during this time. PWUD with mobility issues, who experienced difficulty accessing services and/or those engaged in precarious street-based income generation were more likely to report food insecurity. Food security is paramount to the success of interventions to prevent COVID-19 and drug toxicity deaths. These findings suggest a need for a more unified state response to food insecurity that prioritises and incorporates accessibility and autonomy of the communities they serve.